Some Characterizations of Weighted Bloch Space (European Journal of Pure and Applied Mathematics, 2009)
In this paper we introduce a new space, the so called $Q_{K,ω}$ space of analytic functions on the unit disk in terms of nondecreasing functions. The relation between integral norm of $Q_{K,ω}$ space and integral norm of the weighted Bloch space ${\cal B}_ω$ is also given.